Patient Comprehension of Common Orthopedic Terminology - Filip Cosic; Lara Kimmel; Elton Edwards (SLACK Incorporated, 2019)
Background: Medical terminology is often complex and confusing to lay people. Even common terms used by health care professionals often have other meanings and can easily be misinterpreted. Objective: This study aimed to identify patient comprehension of common orthopedic terminology across multiple hospital settings. Methods: A cross-sectional study was conducted from September 2016 until November 2016 at an Academic Level 1 trauma center. One hundred and fifty emergency department patients and 150 orthopedic inpatients with isolated orthopedic injuries were included. Participants completed a questionnaire consisting of 12 multiple-choice questions determining patient comprehension of common orthopedic terminology. Key Results: Total comprehension scores on the questionnaire were scored as number correct out of 11. In the emergency department, the mean total score was 5.01 compared to 5.45 in orthopedic inpatients (p = .046). Patients in both groups demonstrated poor understanding of medical terms (including fracture, ruptured tendon) and anatomical terms. In contrast, nonmedical terminology such as broken bone was better understood. Fifty-seven percent of participants stated that they understood their orthopedic condition completely. Notably, there was no correlation (r = .15) between comprehension and participants describing that they completely understood their orthopedic condition. Conclusions: Emergency department patients and orthopedic inpatients demonstrate poor comprehension of orthopedic terminology. Health care professionals should assume a poor level of comprehension during their interactions with orthopedic patients and ensure that patient communication is clear, concise, and informative to facilitate better patient comprehension, informed consent, and an improved doctor-patient relationship.